Linguistic Agency and Emotional Lexicon in Jane Eyre: A Corpus-Assisted Literary Analysis for English Language Teaching - Muliyani Muliyani; Harlinah Sahib; Rahmawati Azi; Bahmansyur Bahmansyur (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study investigates the construction of linguistic agency and emotional expression in Jane Eyre by Charlotte Brontë through a corpus-assisted stylistic approach. The research aims to examine how syntactic structures, modality, pronoun usage, and emotional vocabulary reflect the protagonist’s psychological transformation and evolving identity throughout the narrative. The study employs a qualitative descriptive design supported by corpus-assisted analysis within the framework of Systemic Functional Linguistics (SFL). The corpus was constructed from the complete text of the novel, consisting of approximately 183,000 words, from which 450 linguistic units and 1,248 clauses were purposively selected and analyzed across three narrative phases: childhood, adolescence, and adulthood. The findings reveal a significant shift from passive to active constructions, indicating the development of linguistic agency and self-determination. The analysis of modality demonstrates an increasing use of volitional expressions such as will and shall, reflecting stronger interpersonal authority and autonomy. Furthermore, the emotional lexicon evolves from expressions associated with fear, sorrow, and repression toward vocabulary emphasizing freedom, hope, independence, and self-worth. These findings suggest that language functions as an important mechanism for the construction of identity, agency, and emotional transformation within literary discourse. The study also highlights the pedagogical relevance of corpus-assisted literary analysis in English Language Teaching (ELT), particularly in fostering students’ linguistic awareness and critical interpretation of literary texts.